Case Report: A novel de novo SPI1 mutation identified in a Chinese patient with agammaglobulinemia - Peng, Qi; Deng, Ming; Zeng, Xiaomei; Cheng, Qingqiu; Xie, Mingyu; Li, Siping; Lu, Xiaomei (Frontiers in Immunology, 2025)
BackgroundPU.1 deficiency, also known as Autosomal Dominant Agammaglobulinemia-10 (AGM10), is a rare primary immunodeficiency caused by mutations in the SPI1 gene, leading to B cell deficiency and hypogammaglobulinemia. To date, human cases of SPI1-related immunodeficiency have been reported in only a limited number of publications, highlighting the scarcity of clinical data and the importance of further characterization.Case descriptionWe describe a Chinese patient with recurrent respiratory infections, agammaglobulinemia, and profound B cell lymphopenia. Initial genetic screening using a targeted Primary Immunodeficiency Panel did not identify any related pathogenic variants. Subsequent whole-exome sequencing revealed a novel de novo nonsense mutation in the SPI1 gene(NM_003120.3:c.130G>T, p.Glu44Ter). The patient subsequently underwent hematopoietic stem cell transplantation (HSCT). Immunological recovery progressed favorably, with B-cell reconstitution and normalization of immunoglobulin levels occurring by approximately 10 months post-HSCT. However, the clinical course was complicated by severe viral meningoencephalitis occurring around two months post-HSCT, which presented as recurrent fever. Cerebrospinal fluid analysis confirmed infection with cytomegalovirus (CMV) and torque teno virus (TTV). This infection resulted in progressive neurological deterioration and permanent paralysis.ConclusionWe report the first Chinese case of PU.1 deficiency caused by a novel SPI1 mutation. Our finding reinforces the need to include SPI1 in diagnostic panels for agammaglobulinemia. Moreover, the severe viral meningoencephalitis after HSCT, despite immune reconstitution, underscores the critical need for aggressive peri-transplant surveillance.